Paediatric computed tomography diagnostic reference levels in Africa: A systematic review - Emmanuel Gyan; Christiana Subaar; George Edusei; Linda Antwi Nyarko (Journal of Medical Radiation Sciences)
Abstract Introduction Improvements in computed tomography (CT) technology in terms of image quality and reduction in absorbed dose have increased its applications in medical imaging. Diagnostic reference levels (DRLs) help to identify high radiation doses that are unusually delivered to patients undergoing exposure to ionising radiation. The aim of this review was to provide an overview of published studies by African researchers towards establishing paediatric CT DRLs in Africa. Methods The search for articles was conducted using some relevant literature search engines including PubMed, Scopus, Science Direct, Google Scholar and Web of Science. Two reviewers were involved in the article selection process which involved a three‐stage screening process of identifying; article titles, abstracts and full‐test reading. Results One hundred and seventy‐four articles were identified from the database, PubMed (30), Scopus (21), Google Scholar (53), Web of Science (25) and Science Direct (45). Fifty duplicated articles were excluded before screening. Twelve peer‐reviewed articles were included in this study based on the inclusion criteria. DRL values in terms of computed tomography dose index volume of head for the age groupings 0–1, 1–5, 5–10 and 10–15 were 27, 36.6, 39.5 and 47.5 mGy while the dose length product values were 461.6, 664, 872 and 978 mGy.cm respectively. The DRLs were calculated as 75th percentile of the local DRLs reported by the 12 articles included in this review. Conclusion This review has shown that only few of the African countries (19%) have published studies on paediatric CT DRLs. There were variations in the DRLs published by the various authors which indicate that harmonisation and standardisation of paediatric CT protocols is essential for the optimisation of paediatric doses.